Transit Oriented Development (TOD) Development in Senen Area, Central Jakarta, Indonesia - Taki, Herika Muhamad; Aliah Amelia; Nathania Azarine; Lubis, Muhammad Zainuddin (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
Senen area, Central Jakarta, is a strategic area that faces various problems, such as traffic congestion, lack of integration between modes of transportation, and minimal facilities for pedestrians and public transportation users. This study aims to evaluate the application of the TOD concept in the Senen area based on principles such as transportation integration, mixed land use, and pedestrian connectivity. This study uses a qualitative descriptive method approach , where the data used is secondary data obtained through literature studies. Literature studies are conducted by referring to previous studies and relevant institutional reports. The data collected includes spatial information, such as maps and geographic data, as well as non-spatial information, such as planning documents and policies. The results of the study indicate that the Senen area has great potential to be developed as a TOD area. Some steps that can be taken include improving connectivity between modes of transportation, improving public facilities, and adding green open spaces. In conclusion, the implementation of TOD in the Senen area can reduce the use of private vehicles, increase the efficiency of public transportation, and create a more comfortable and environmentally friendly city environment.